Insecticide resistance status and high frequency of kdr mutations in Aedes aegypti in Tegucigalpa, Honduras - Cindy Reyes-Perdomo; Denis Escobar; Luis Galo; Oscar Urrutia; Rita Lucrecia Vizcaino; Audrey Lenhart; Gustavo Fontecha (Parasites & Vectors)
Abstract Background Aedes aegypti is the main vector of arboviruses in the Americas. Insecticide use remains the primary method for outbreak control, but prolonged application exerts selective pressure that promotes resistance. This study aimed to assess insecticide resistance and characterize key knockdown resistance (kdr) mutations in Ae. aegypti populations from the Central District of Honduras. Methods Larvae were collected from four localities between May and June 2023. Susceptibility to four insecticides was evaluated via bioassays. Frequencies of the F1534C and V1016I kdr alleles and their haplotypes were determined, and sequencing of the vgsc gene was performed for further genotyping. Results A total of 1592 Ae. aegypti females were phenotyped. All populations were resistant to permethrin and malathion, and two were resistant to deltamethrin; all were susceptible to bendiocarb. The 1534C mutant allele was fixed (1.0), and 1016I had an overall frequency of 0.89, with local variation from 0.48 to 1.0. Conclusions Widespread resistance to commonly used insecticides was detected in Ae. aegypti from the Central District. High frequencies of kdr mutations underscore the need for continuous resistance monitoring to guide effective vector control strategies in Honduras. Graphical abstract